Pedagogy, politics and philosophy of peace : interrogating peace and peacemaking - Borg, Carmel; Grech, Michael (London ; New York, NY : Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2018)
'In an age where official and sponsored violence are becoming normalised and conceived of as legitimate tools of peace keeping, a number of leading academics and activists represented in Pedagogy, Politics and Philosophy of Peace interrogate and resist the intensification of the militarisation of civil life and of international relations. Coming from different areas of study, the contributors to this volume discuss peace and critical peace education from a range of perspectives. The nature of peace, myths related to peace, the logistics of peace and peace-making as well as the relation of peace and pedagogy in the broadest meaning of the term constitute the main themes of the book. The common thread that binds the chapters together is the distinction between genuine/ authentic and false peace and the importance of critical reflection on actions that contribute to genuine peace.'--
Part 1. The Contents of Peace. Where Does True Peace Dwell? / Marianna Papastephanou -- A Gramscian Analysis of Passive Revolution and its Contribution to the Study of Peace /Joseph Gravina -- Breathing Peace, Relating with the Other and the Maternal / Simone Galea -- The Limits of Exogenous Initiatives in Peacemaking, Focusing on Iraq after the US Invasion / Arsalan Alshinawi -- Critical Peace in the Digital Era of Austerity and Crisis / Nicos Trimikliniotis and Dimitris Trimithiotis -- Part 2. Challenges to Peace Education. Dreaming of Peace in a Culture of War / Antonia Darder -- The Myth of the Inevitability of War / Clive Zammit -- Liberal Peace and Media Debates around the Cases of Jyllands-Posten and Charlie Hebdo / Carmen Sammut -- Part 3. Pedagogy of Peace. Some Reflections on Critical Peace Education / Michalinos Zembylas and Zvi Bekerman -- School Textbooks and Entanglements of the'Colonial Present' in Israel and Palestine / Andre Elias Mazawi -- The Long Shadow Thrown over the Actions of Men / Michael Zammit -- Schooling for Democracy : Music and Critical Pedagogy in Egypt / Linda Herrera -- Epilogue / Carmel Borg and Michael Grech.
Includes bibliographical references and index.
Keywords: Peace -- Study and teaching; Peace-building -- Study and teaching; Critical pedagogy; Education -- Philosophy